Screening of COVID-19 Using Rapid Test Before Gastrointestinal Procedures; Experience in a Limited Resource Hospital - Yusuf, Fauzi; Maghfirah, Desi; Muhsin, Muhsin (JSMARTech: Journal of Smart Bioprospecting and Technology, 2020)
Corona Virus Disease 2019 (COVID-19) is an emerging disease announced by World Health Organization (WHO) as a pandemic disease since March 2020. Several international guidelines suggested use of reverse transcriptase polymerase chain reaction (RT-PCR) test as screening tool before starting gastrointestinal (GI) procedures. Although RT-PCR is a gold standard, it has limitation as it is expensive and requires special expertise therefore difficult to implement in limited resource hospitals. Due to lack of RT-PCR tests available and in accordance with Indonesian government regulation, thirty patients in a tertiary referred hospital in Banda Aceh were screened with rapid test antigen and antibody for COVID-19 before underwent emergency and urgency GI procedures such as endoscopy, colonoscopy and abdominal ultrasonography. Several laboratory parameters and chest X-ray in all patients were assessed. All health care workers in procedure room were also tested with rapid antigen 1 week after the procedures. The study showed that laboratory parameters and chest X-ray were relatively normal for all patients. All procedures were conducted safely and leave no new COVID-19 case amongst health care workers. In conclusion, rapid test can be used in hospitals with limited resources, although RT-PCR test is still needed to confirm COVID-19 cases. Safe GI procedures can still be performed in limited resource hospital, although the possibility for disease transmission is still high. A modified guideline is needed in these hospitals in order to conduct safe GI procedures.